An Analytical Study of AI Integration Readiness Among Primary School Teachers in Jepara - Nahar, Afifatun; Muhaimin, Muh; Rohman, Nur (Jurnal Gentala Pendidikan Dasar, 2025)
This research aims to analyze the preparedness of elementary school teachers in Jepara Regency to integrate artificial intelligence (AI) into classroom learning. The method used is mixed methods with a convergent design, combining quantitative data through questionnaires and qualitative data through interviews and observations. A total of 30 elementary schools were randomly selected from 572 elementary schools, with 80 teachers as respondents. The results of the study indicate that the majority of teachers have an understanding and positive attitude towards AI, as well as high motivation to use it in learning. However, technical skills and AI utilization vary. The use of AI is still dominant in administrative aspects, while its utilization in learning activities remains limited. The main challenges faced include a lack of training, infrastructure limitations, and the need for policy support. The recommendations from this research emphasize the importance of continuous training, strengthening digital infrastructure, and collaboration between teachers, schools, and the government to ensure the successful implementation of AI in basic education.